Effortless Calculations of Arithmetic Progression Through Vedic Sutras - Singh, S. R.; Yadav, Rashmi (Journal of Informatics and Mathematical Sciences, 2025)
To finding the \(n\)th term and the sum of \(n\) terms in Arithmetic Progression is very easy if the number of term’s small but the it is bulky if the number of term’s are lager and so its take’s larger time and also take our large affects and difficulties. On the other hand, the Vedic Mathematics work’s opposite as the modern mathematics so if we using the Vedic Mathematics sutra \(^3\)Urdhwatiryagbhyam, sutra \(^7\)sankalan-vyavkalanabyam, Up-sutra \(^9\)Antyyoravto finding the \(n\)th term and the sum of \(n\) terms in Arithmetic Progression it takes our large affects reduced around 60-65% and also take’s small time comparatively modern mathematics. The arithmetic pattern is one of the easiest series to study. It contains adding or subtracting from a common difference \((d)\), for generating a string of the numbers that are interrelated to each other. Thus, in this document we present the comparison to find the \(n\)th term and the sum of \(n\) terms in Arithmetic Progression by using the modern mathematics and Vedic mathematics.